The Great Shelby Holmes meets her match - Eulberg, Elizabeth (The Great Shelby Holmes, 2017)
Nine-year-old Shelby Holmes and eleven-year-old John Watson team up again, this time to investigate the new science teacher at the Harlem Academy of the Arts.